Assessment of genetic diversity and population structure of fragrant rose (Rosa × hybrida) cultivars using microsatellite markers - V, APARNA; BHAT, K V; JANAKIRAM, T; PRASAD, K V; RAJU, D V S; P, SAPNA; NAMITHA, NAMITHA; SINGH, KANWAR P (The Indian Journal of Agricultural Sciences, 2019)
Rose (Rosa Ã— hybrida L.) is a commercially important ornamental crop which represents major share in world floriculture market and essential oil industry. In the present investigation, genetic diversity among 25 fragrant rose cultivars belonging to exotic and Indian origin was studied during 2016-17 at New Delhi. Thirty one SSR markers were used for characterization. A total of 96 alleles were identified among the genotypes with an average of 3.9 alleles per loci. Diversity among populations of different origins was analysed and it revealed that, cultivars from Indian origin exhibited higher diversity as compared to the selected cultivars from American and European origin. Effective number of alleles (Ne) and expected heterozygosity (He) values were more in Indian population (Ne=1.93, He=0.49) as compared to selected populations of American (Ne=1.45, He=0.45 and European (Ne=1.29, He=0.29) origin. Matching coefficient values ranged from 0.55â€“ 0.86 indicated the existence of moderate variability among fragrant roses of different origin. Unweighted Pair Group Method using Arithmetic Mean (UPGMA) dendrogram clearly separated all the 25 genotypes into 7 different clusters. Cultivars, Rose Sherbet, Century Two Seedling and Brandy showed distant relationship with other cultivars and were found in three different individual clusters V, VI and VII respectively. The highest and lowest similarity values were noticed between the cultivar sets, Jawahar and Double Delight (86%) and Century Two Seedling and Brandy (55%). The molecular data generated in present investigation would be highly helpful for cultivar identification, conservation and for breeding fragrant roses.